Jean-Marc Bustamante. - Van Abbemuseum, Eindhoven (Eindhoven : Van Abbemuseum Eindhoven, 1995)
This book originated with the exhibition of work by Jean-Marc Bustamante at the Stedelijk Van Abbemuseum in Eindhoven in 1992. It is not, however, an exhibition catalogue in the usual sense. Later works and presentations in other museums are included so that it offers a first overview of his oeuvre.
biog. Bustamante, biog. Danielle Cohen-Levinas flaptekst
Engels
Exhibition. Jean-Marc Bustamante. Van Abbemuseum Eindhoven. 1992-05-16. 1992-07-12
boek
Keywords: Bustamante, Jean-Marc